1999
DOI: 10.1080/026870399401993
|View full text |Cite
|
Sign up to set email alerts
|

Narrative discourse following severe traumatic brain injury: a longitudinal follow-up

Abstract: This paper describes the narrative discourse abilities of a group of severely traumatically brain injured (TBI) speakers at two intervals post-injury. At initial assessment (between 3 and 6 months post-injury) a group of 26 TBI speakers were assessed using a picture description task. The performance of two control groups was also examined. The ®rst control group was comprised of 26 non-TBI orthopaedically injured speakers and the second control group comprised 26 university students. These control groups were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 35 publications
1
29
0
Order By: Relevance
“…With respect to neural substrates, both these processes, attentional control and task management, are mediated by the prefrontal cortex and its circuitry (Miller, 2000). Again, these behaviours have been reported by previous researchers in the area (e.g., Galski, Tompkins, & Johnston, 1998;McDonald & Pearce, 1996;Snow et al, 1999). Further, the validity of Factor 4 was supported by significant correlations with severity of injury for both self and close other reports.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…With respect to neural substrates, both these processes, attentional control and task management, are mediated by the prefrontal cortex and its circuitry (Miller, 2000). Again, these behaviours have been reported by previous researchers in the area (e.g., Galski, Tompkins, & Johnston, 1998;McDonald & Pearce, 1996;Snow et al, 1999). Further, the validity of Factor 4 was supported by significant correlations with severity of injury for both self and close other reports.…”
Section: Discussionsupporting
confidence: 69%
“…Given the complexity and unpredictability of everyday discourse, no single tool or procedure is likely to provide clinicians with an ecologically valid representation of a client's conversational competence (Douglas, Bracy, & Snow, in press;. Many methods have been applied to discourse analysis following TBI, including analysis of cohesion (Hartley & Jensen, 1991;Mentis & Prutting, 1991), story grammar (Coelho, Liles, & Duffy, 1995;Snow, Douglas, & Ponsford, 1999), sociolinguistic analysis (Togher, 2000;Togher et al, 1997), and Clinical Discourse Analysis (Snow et al, 1997(Snow et al, , 1998. All of these methods require elicitation of representative discourse samples and transcription in order to apply specific analysis protocols.…”
mentioning
confidence: 99%
“…This picture stimulus 2 has been used in previous studies investigating language impairment, e.g. in people with traumatic brain injury (Hartley & Jensen, 1991;Snow et al, 1999) and in people recovering from stroke (e.g. Davis et al, 1997).…”
Section: Methodsmentioning
confidence: 99%
“…interactive) discourse is difficult to standardise, and timeconsuming to measure (Snow et al, 1999) narratives have been identified as a potentially more efficient measure of spoken language. According to Stein and Glenn (1979) well developed narrative comprises seven logically sequenced story grammar elements (a setting, an initiating event, an internal response, a plan of action, an attempt at action, direct consequences of this action, and protagonists' reactions).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation